(untitled) (Raparin Journal of Humanities (RJH), 2025)
After intense negotiations between the migrants and supporters the issue of the appointment of the caliph was resolved, but the appointment of the second caliph was different from the other three caliphs. Abu Bakr wanted the issue to be resolved before his death. Therefore, in consultation with the close companions of the Prophet (peace be upon him), he appointed (Umar ibn al-Khattab) as the Crown Prince. Especially the Umayyad caliphs and those scholars who considered the succession system as part of the Islamic system of rule, which brought about the consequences of seizing the throne of the caliphate and oppression. Umar’s appointment was consistent with the conditions set for the caliph, but differed in terms of appointment procedures. However, in terms of reaction, the appointment of Caliph Umar was the best consensus compared to the others, the duration of the caliphate is considered the golden age. Because of Umar did not propose anyone after him, for this purpose he kept his relatives away from him, entrusted him to a council of six members and provided the opportunity for consultation and interested discussion. Omar ibn al-Khattab is known as the founder of the group advisory caliphate, but opposed the imposition and neglect of advisory. In this study, we have analyzed this issue in five sections and reached the following conclusions: the first section is the process of appointing Omar as Caliph, the second topic is the details of the process, the third topic is comparison of conditions and procedures Between the two types of advisory caliphate and the succession caliphate, the final part of criticism was the appointment of ’Umar.